2010
DOI: 10.2174/1874944501003010001
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital, Gender and Educational Level Impact on Self-Rated Health~!2009-09-17~!2010-03-11~!2010-05-26~!

Abstract: Abstract:Objectives: Social capital has been recognized as one important social determinant for health, but we still have limited knowledge about how it can be used to explain inequality in health. This study investigated the links between individual social capital and self-rated health by gender and educational level, and analyzed if access to social capital might explain the observed disparities in self-rated health between men and women and different educational groups. Study design: A cross-sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 41 publications
6
52
2
1
Order By: Relevance
“…trust safety and reciprocity norms), compared to structural forms (Eriksson et al 2010;Harpham et al 2004;Kim et al 2008;Nyqvist et al 2008;Yip et al 2007). Current evidence also indicates that social capital is not a resource equally accessible to all population groups.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…trust safety and reciprocity norms), compared to structural forms (Eriksson et al 2010;Harpham et al 2004;Kim et al 2008;Nyqvist et al 2008;Yip et al 2007). Current evidence also indicates that social capital is not a resource equally accessible to all population groups.…”
Section: Introductionmentioning
confidence: 98%
“…Studies from Indonesia (Silvey and Elmhirst 2003) and the UK (Campbell et al 1999) have found that women tend to be more involved in local close-knit bonding networks compared to men, while a study from Northern Sweden (Eriksson et al 2010) found the reverse; women were more involved in bridging social networks compared to men. The same study (Eriksson et al 2010) additionally found that women were less likely to have access to safety compared to men. Likewise, studies have shown that older people tend to feel less safe in their neighbourhoods compared to younger people (Jeffords 1983).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SRH is used in research on various topics, but in particular in longitudinal studies as a predictor of subsequent mortality [1][2][3]; in cross-sectional surveys as the outcome variable in studies on social inequalities in health [4][5][6][7][8]; and in studies on compression of morbidity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%